2019
DOI: 10.1371/journal.pone.0222846
|View full text |Cite
|
Sign up to set email alerts
|

Animal-assisted therapy for patients in a minimally conscious state: A randomized two treatment multi-period crossover trial

Abstract: ObjectiveTo investigate if animal-assisted therapy (AAT) leads to higher consciousness in patients in a minimally conscious state during a therapy session, measured via behavioral reactions, heart rate and heart rate variability.MethodsIn a randomized two treatment multi-period crossover trial, 10 patients in a minimally conscious state participated in eight AAT sessions and eight paralleled conventional therapy sessions, leading to 78 AAT and 73 analyzed control sessions. Patients’ responses during sessions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
1
6

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 29 publications
4
16
1
6
Order By: Relevance
“…This effect is probably driven by a stronger encoding and is found for both positive and negative emotions [ 10 ]. It was shown that memory is especially enhanced by emotions driven by stimuli that have a high emotional relevance for us [ 11 , 12 , 13 , 14 ]. Humans develop close emotional bonds and relevant social relationships with animals [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect is probably driven by a stronger encoding and is found for both positive and negative emotions [ 10 ]. It was shown that memory is especially enhanced by emotions driven by stimuli that have a high emotional relevance for us [ 11 , 12 , 13 , 14 ]. Humans develop close emotional bonds and relevant social relationships with animals [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that AAT can lead to enhanced social behaviour, positive emotions and therapy motivation in patients with acquired brain injury [ 20 ]. In patients in a minimally conscious state, the presence of an animal can lead to more behavioural reactions and increased physiological arousal compared to control sessions [ 14 ]. However, there are no studies investigating long-term effects of AAT on memory in patients with acquired brain injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,6,[17][18][19][20] A first study on animal-assisted therapy on patients in minimally conscious state found increased behavioral reactions and physiological arousal during animalassisted therapy sessions compared with control therapy sessions. 21 Apart from this study, only anecdotal data exist regarding animal-assisted therapy for patients with severe neurological illnesses like disorders of consciousness. 22,23 There is a lack of research investigating for which patients with severe neurological impairments animal-assisted therapy might be an option, how the therapy should be conducted, or what effects this therapy form might have.…”
Section: Introductionmentioning
confidence: 99%
“…This illustrates why animals are seen as helpful partners within therapy for patients with disorders of consciousness. In a first controlled study, Hediger and colleagues showed beneficial effects of AAT in patients in a MCS compared to control therapy sessions (11). Beside such quantitative research on this topic it is crucial to learn for what patients AAT could be a promising approach and understand the individual reactions of patients.…”
Section: Introductionmentioning
confidence: 99%